Isolation and pathogenicity of a novel recombinant pseudorabies virus from the attenuated vaccine and classical strains - Zhang, Zhendong; Wei, Qingteng; Wu, Chengyue; Ye, Zhengqin; Qin, Liting; Chen, Ting; Sun, Zhe; Tian, Kegong; Li, Xiangdong (Frontiers in Veterinary Science, 2025)
Pseudorabies (PR) remains one of the most important swine diseases in China. Live attenuated vaccines have been widely deployed and have proven highly effective in controlling PR in the field. However, recent concerns regarding the evolution and recombination events involving pseudorabies virus (PRV) vaccine strains have raised substantial attention. In the present study, a novel recombinant PRV strain named HN2201 was isolated from one stillbirth case in Henan province in 2022. To assess the genetic and evolutionary features, the major immunogenic and virulence-associated genes, including gB, gC, gD, gG, gE and TK, were sequenced and analyzed. Phylogenetic and nucleotide homology analysis revealed that gB, gC, gD and gG genes of HN2201 displayed close relationship with Chinese classical strains. However, the TK gene of HN2201 contained a continuous deletion of 205 nucleotides, sharing the highest nucleotide homology (99.9%) with HB-98 vaccine strain. Additionally, a similar deletion was observed in the promoter region of the gE gene in both HN2201 and HB-98. Pathogenicity studies on 9-week-old piglets demonstrated that HN2201 exhibited attenuated virulence, characterized by transient clinical signs. The above results suggest that the naturally isolated HN2201 likely resulted from recombination events between the PRV classical strain and the HB-98 vaccine strain. Our findings provide valuable insights into the evolution of PRV in China and underscore the necessity of scientific and cautious use of PRV vaccines in the field.